2006
DOI: 10.1002/app.22885
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of irradiated PTFE micropowder with methacryl‐ or hydroxy groups for chemical coupling of PTFE with different matrix polymers

Abstract: This article describes the modification of electron beam irradiated polytetrafluoroethylene (PTFE) material (500 kGy) into a functionalised micropowder, bearing methacrylate or hydroxy groups. The aim of this work is to achieve compatibilization of modified PTFE in a variety of matrix polymers, such as elastomers and duromers. It is well known that irradiation of high molecular PTFE in the presence of air, followed by annealing with water vapor, leads to a functionalization of the PTFE micropowder, containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The incorporation of surface functional groups changes the surface energy and polarity of the PTFE; thereby enabling the formation of inter-molecular forces and leading to an improved dispersion in the composite. Lehmann et al [14,18,19] altered PTFE micro-powders by means of electron beam irradiation to incorporate functional groups for subsequent use in different polymer matrices. However, Shojaei et al [16] have pointed out that not only the radiation beam equipment is expensive; the process in itself is quite difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of surface functional groups changes the surface energy and polarity of the PTFE; thereby enabling the formation of inter-molecular forces and leading to an improved dispersion in the composite. Lehmann et al [14,18,19] altered PTFE micro-powders by means of electron beam irradiation to incorporate functional groups for subsequent use in different polymer matrices. However, Shojaei et al [16] have pointed out that not only the radiation beam equipment is expensive; the process in itself is quite difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…Polytetrafluoroethylene (PTFE) offers outstanding properties such as high chemical inertness, heat resistance and excellent dielectric properties. Owing to its low coefficient of friction, PTFE is widely used as a sintered pure polymer, a reinforcement polymer and as an additive in polymer compounds to improve the friction and wear properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. However, in some cases, its applications are hampered due to PTFE’s inherent poor chemical reactivity, low wettability and poor adhesion with other materials [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known that the double bonds in the chloroprene microstructure are sufficiently deactivated by electronegative chlorine atom so that the direct chemical coupling with PTFE powder by the radical coupling mechanism is implausible. However, very recently it has been shown that further functionalization of the electron-irradiated PTFE powder with functional groups such as methacryl or hydroxyl groups for chemical coupling with different matrix polymers is possible [16]. In the present study, PTFE powder produced by electron irradiation bearing -COOH groups have been functionalized in the presence of zinc oxide for chemical coupling with chloroprene rubber.…”
Section: Introductionmentioning
confidence: 97%